Gut Microbiota of Individuals Could Be Balanced by a 14-Day Supplementation With Laminaria japonica and Differed in Metabolizing Alginate and Galactofucan - Zhang, Xueqian; Su, Changyu; Cao, Cui; Gong, Guiping; Huang, Linjuan; Wang, Zhongfu; Song, Shuang; Zhu, Beiwei (Frontiers in Nutrition, 2022)
Laminaria japonica is rich in alginate (Alg) and galactofucan (GF) which have been both reported to regulate microbiota composition. In order to reveal the effect of L. japonica on human gut microbiota, the fecal microbiota of 12 volunteers before and after 14-day L. japonica intake were sequenced and compared, and the capabilities of the gut microbiota to utilize Alg and GF were also investigated. The 16S rRNA gene sequencing results demonstrated that Firmicutes/Bacteroidetes ratio could be balanced by L. japonica supplementation. The ability of gut microbiota to utilize Alg was significantly enhanced by L. japonica supplementation. Further multiple liner regression analysis suggested that bacteria from Bacteroidaceae and Ruminococcaceae were positively correlated with Alg utilization while those from Erysipelotrichaceae, Bacteroidaceae and Prevotellaceae participated in GF degradation. Moreover, the production of acetic acid and the total SCFAs in fermentation were consistent with the consumptions of Alg and GF, and propionic acid content was positively correlation with Alg consumption. In addition, the percentage of monosaccharide in the consumed GF after the fermentation suggested gut microbiota from individuals could consume GF with different monosaccharide preferences. These findings shed a light on the impacts of dietary Laminaria japonica on human health.